Development of academic entrepreneurship in an innovative economy: factors and motivation - Sitenko, D.A.; Holienka, М.; Sabyrzhan, A.; Gartsuyeva, Ye.V. (BUKETOV BUSINESS REVIEW, 2023)
Object: Study of issues of entrepreneurial activity motivation among university scientists and identification of factors influencing academic entrepreneurship. Methods: The study uses the methods of system analysis, comparative analysis, grouping method, content analysis, analysis of literature. Findings: The article considers the main factors that influence university scientists when they make a decision on academic entrepreneurship. The types of activities that can be attributed to academic entrepreneurship are identified: the implementation of funded projects, the foundation of start-ups, licensing, etc. An analysis of the studies conducted in the field of motivation of academic entrepreneurs made it possible to identify groups of main factors, as well as the strength of their influence on the motivation of scientists. Among the personal motives most often in Western research scientists highlight the desire to continue research, create innovative products, scientific interest in their field of study. Conclusions: The creation of an innovative infrastructure and legislation in the field of intellectual property protection and technology transfer largely determines the possibilities for the development of academic entrepreneurship in the country. Scientists involved in the commercialization of scientific developments become an example (mentor) for younger colleagues, which makes it possible to involve young, qualified specialists in academic entrepreneurship. The presence of professional connections and the opportunity to communicate with business representatives greatly facilitates the receipt of funding for the implementation of results, makes small innovative enterprises more successful in the market. Despite the small percentage of academic entrepreneurs in universities, most scientists maintain contacts with the business community, which, under favorable conditions, can develop into entrepreneurial activity.